Immune Response Modulation by Caliciviruses - Peñaflor-Téllez, Yoatzin; Trujillo-Uscanga, Adrian; Escobar-Almazán, Jesús Alejandro; Gutiérrez-Escolano, Ana Lorena (Frontiers in Immunology, 2019)
Noroviruses and Sapoviruses, classified in the Caliciviridae family, are small positive-stranded RNA viruses, considered nowadays the leading cause of acute gastroenteritis globally in both children and adults. Although most noroviruses have been associated with gastrointestinal disease in humans, almost 50 years after its discovery, there is still a lack of comprehensive evidence regarding its biology and pathogenesis mainly because they can be neither conveniently grown in cultured cells nor propagated in animal models. However, other members of this family such as Feline calicivirus (FCV), Murine norovirus (MNV), Rabbit hemorrhagic disease virus (RHDV), and Porcine sapovirus (PS), from which there are accessible propagation systems, have been useful to study the calicivirus replication strategies. Using cell cultures and animal models, many of the functions of the viral proteins in the viral replication cycles have been well-characterized. Moreover, evidence of the role of viral proteins from different members of the family in the establishment of infection has been generated and the mechanism of their immunopathogenesis begins to be understood. In this review, we discuss different aspects of how caliciviruses are implicated in membrane rearrangements, apoptosis, and evasion of the immune responses, highlighting some of the pathogenic mechanisms triggered by different members of the Caliciviridae family.